HUBUNGAN DUKUNGAN KELUARGA DAN TENAGA KESEHATAN DENGAN MOTIVASI KESEDIAAN MASYARAKAT MENERIMA VAKSIN COVID-19 DI DESA ANGGRASMANIS KABUPATEN KARANGANYAR - Taen, Cindy Valla; Sari, Dian Nur Adkhana; Suryati, Suryati; Setyaningrum, Niken (Coping: Community of Publishing in Nursing; Vol 11 No 5 (2023): Oktober 2023DO - 10.24843/coping.2023.v11.i05.p08, 2023)
2019 was shocked by the outbreak of a new virus, namely Covid-19. One possible strategy to stop the spread of this virus is to produce a vaccine. Vaccines are the last line of defense against infectious diseases. The main obstacle to using the Covid-19 vaccine is people's disbelief in preventing Covid-19 vaccination. The desire to get the Covid-19 vaccine is influenced by several things including family support and support from health workers. With the motive of community readiness to get the Covid-19 vaccination, this study seeks to find out the relationship between family support and health workers in Anggramanis village, Kecamatan Jenawi Kabupaten Karanganyar. This type of research is quantitative, the sample size is 290 respondents and the sampling technique is accidental sampling. Data collection was carried out from May 27 to June 10, 2022. Data testing used the chi square analysis test and multiple linear regression. This study used three research instruments, namely the family support questionnaire, the health worker support questionnaire, and the motivational questionnaire on the willingness to accept the Covid-19 vaccine. The results of the chi square test obtained a value of p = 0,000 and a contingency value of 0,406 (family support) and 0,349 (support of health workers). Thus there is a relationship between family support and health workers with the motivation of the community's willingness to receive the Covid-19 vaccine in Anggramanis Village Kecamatan Jenawi Kabupaten Karanganyar.